Development of Physics E-LKPD Using Augmented Reality (AR) Based LOK-R ‎Model on Students' Critical Thinking Skills - Rizka Dwi Maretha‎; Irwandani; Vandan Wiliyanti (ISEJ : Indonesian Science Education Journal, 2025)
This study was conducted to develop an Electronic Student Worksheet (E-LKPD) based on Augmented Reality (AR) with the LOK-R (Literacy, Orientation, Collaboration, Reflection) model for Physics on thermodynamics material for grade XI students and to test its effectiveness in improving students' critical thinking skills. The research method used was Research and Development (R&D) with the 4D development model, but limited to the development stage (3D). Data collection methods involved non-test instruments (observation sheets and questionnaires) and a 10-item essay test. The results of the study indicate that: (1) The AR-based Physics E-LKPD with the LOK-R model is highly suitable for use in thermodynamics learning for high school students with a "Very Good" category based on expert validation; (2) The developed E-LKPD can improve students' critical thinking skills (N-gain = 0.73) with a "High" category; and (3) This E-LKPD is effective for learning thermodynamics topics regarding students' critical thinking skills.